Validation of the Sport Multidimensional Perfectionism Scale-2 for the mexican sport context - Pineda-Espejel, A.; Arrayales, E.; Morquecho-Sanchez, R.; Trejo, M. (International Journal of Human Movement and Sports Sciences, 2017)
The aim of this study was to validate the factorial structure of a Spanish version of the Sport Multidimensional Perfectionism Scale-2 (Sport-MPS-2) for the Mexican population, and provide evidence of reliability. This scale is composed of 42 items that measure six factors of perfectionism: concern over mistakes, organization, perception parental pressure, perception coach pressure, doubts about actions, and personal standards. Such factors were suggested by the multidimensional perfectionism approach. The study involved 420 athletes of both genders with an average age of 21.63 years old (SD = 3.83) who answered the Mexican Spanish Version of the Sport-MPS-2. After eliminating six items, the results supported the six-factor model; and in five factors, the internal consistency exceeded or was under the limit of the usage criteria. In conclusion, the Mexican Spanish version of the Sport-MPS-2 offers factorial structure and constructs validity, excluding six items. Thus, it can be used for assessing five dimensions of perfectionism in athletes, even though further research shall be conducted to improve this instrument.